Abundant Bodies in Times of Excess: A Critical Exploration of Fatness from Cairo to Tokyo - Aly, Sarah (AUC Knowledge Fountain, 2024)
This work is an autoethnographic exploration of the social construction of fatness in contexts of existing and emerging neoliberal state control through the embodied experiences of fat people, following the tradition of ‘fat epistemology’ promoted by the emerging 'critical fat studies' field. It is a comparative study of the experiences of fatness as an unstable embodied category of being, rather than a liminal undesirable state or medical condition, in Cairo, Alexandria, and Tokyo, paying particular attention to the gender, racial, and class dynamics surrounding the construction (and marginalization) of fatness across various spatial and temporal contexts. These experiences are considered in conversation with the urban landscapes inhabited by each interlocutor, and comparative media representations of fatness in Egypt and Japan (media including television shows, commercials, and public comments made by government officials), as well as an exploration of the historical moments oft-referenced in modern debates surrounding the body in both contexts.